An online database and desktop assessment software to simplify systematic reviews in environmental science. (February 2015) - Webb, J. Angus; Miller, Kimberly A.; Stewardson, Michael J.; de Little, Siobhan C.; Nichols, Susan J.; Wealands, Stephen R.
Abstract: We describe software to facilitate systematic reviews in environmental science. Eco Evidence allows reviewers to draw strong conclusions from a collection of individually-weak studies. It consists of two components. An online database stores and shares the atomized findings of previously-published research. A desktop analysis tool synthesizes this evidence to test cause–effect hypotheses. The software produces a standardized report, maximizing transparency and repeatability. We illustrate evidence extraction and synthesis. Environmental research is hampered by the complexity of natural environments, and difficulty with performing experiments in such systems. Under these constraints, systematic syntheses of the rapidly-expanding literature can advance ecological understanding, inform environmental management, and identify knowledge gaps and priorities for future research. Eco Evidence, and in particular its online re-usable bank of evidence, reduces the workload involved in systematic reviews. This is the first systematic review software for environmental science, and opens the way for increased uptake of this powerful approach. Highlights: Systematic review is a powerful, but underused, technique in environmental science. We developed software and a database designed to simplify such reviews. The online database stores and shares evidence, reducing the workload for users. The analysis software guides users through a previously-published review method. The software produces a standard report to maximize transparency and repeatability.